René Girard and Mimetic Theory - Paul Gifford (St Andrews Encyclopaedia of Theology, 2023)
René Girard is not a theologian; he is best described as fundamental anthropologist and culture theorist. His versatile system of hermeneutical and heuristic thinking is known to its author as ‘the Mimetic Theory’. Girardian ‘mimesis’ denotes, in a myriad of particular forms, a structure of reciprocal imitation, actual or potential (‘I hold out my hand, you hold out yours’; ‘do unto others as you would have them do to you’; ‘Thy Kingdom come […]/ On earth as it is in Heaven’). Human mimesis, only recently understood in its neurological basis, is increasingly recognized as enabling what social scientists call ‘group intelligence’. Its structures and processes have deep and ancient roots in pre-human nature, something of interest to the evolutionary sciences; while the New Testament gives mimetic processes pride of place in exploring the nature of discipleship and in understanding spiritual transformation and growth. It also recognizes an ultimate form of loving mimesis operating in the heart of the trinitarian God. From his own private conversion and return to Catholic faith in 1959, the most fundamental vocation of his theory, in Girard’s own eyes, was the elucidation of the deepest and darkest places of the collective religious psyche. His ‘triple audacity’ consists in applying the perspectives and tools of Mimetic Theory to elucidating three of the most central of human enigmas: the origins of religion; the beginnings of culture; and the process of hominization itself. He sees humanity as ‘born out of the religious dimension of things’; containing (in both senses: ‘limiting’, but also ‘retaining within itself’) its own temptation to self-destructive violence through the self-organizing mechanism of emissary victimage (‘scapegoating’), a mechanism subsequently ritualized as ‘sacrifice’. Mimetic theory offers a logic or ‘grammar’ of sacred violence from which ‘primitive’ (archaic-sacral, first-form) religion is seen to emerge; and which, unknown to its actors, still conditions the most diverse and far-flung phenomena of culture and society; even – perhaps especially – in modern, radically secularized times. Mimetic theory as practised by René Girard comes to assume theology as its native complement: both in elucidating the singularity and world-changing significance of Judaeo-Christian revelation as recorded in the Hebrew scriptures and the Christian gospels; and in renewing the great theological drama of salvation, which it shows transcending and transforming Darwinian survival. This is most strikingly the case in the Passion of Christ, in which is re-enacted transformatively the archetypical proto-drama of Girardian ‘founding murder’.